2013
DOI: 10.4314/ijbcs.v7i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and kinetic properties of arginase in the gut of grasshopper (<i>Zonocerus variegatus</i> Linn)

Abstract: Arginase (EC 3.5.3.1) catalyzes the hydrolysis of arginine to ornithine and urea. Arginase was purified and characterized from the gut of Zonocerus variegatus through DEAE-cellulose and biogel-P100 gel filtration chromatography. The specific activity of the enzyme was 3.7 µmoles/min per mg of protein and a yield of 14.7%. An apparent molecular weight of 143,000 daltons was estimated by gel filtration on biogel P-100. The Michaelis constant (K m) of the enzyme was 40 mM with arginine as substrate. The optimum p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…Par ailleurs, au cours de nos inventaires de terrain, nous avons observé la présence de Zonocerus variegatus dans la végétation environnante (Talinum triangulare, Aspilla lacifolis, Aspilla africana, Tridax esculenta, Chromolaena odorata) mais également dans les champs de Manihot esculenta. Les feuilles de ces espèces contribuent a la croissance de Zonocerus variegatus(Okonji et al, 2013) Cela démontre le caractère polyphage du criquet puant. Des études réalisées parJames et al (2015) ont montré que Zonocerus variegatus était attiré par différentes plantes contenants des alcaloïdes de pyrrolicidines dont le criquet s'en sert pour se protéger chimiquement ainsi que ses oeufs contre les parasites.…”
unclassified
“…Par ailleurs, au cours de nos inventaires de terrain, nous avons observé la présence de Zonocerus variegatus dans la végétation environnante (Talinum triangulare, Aspilla lacifolis, Aspilla africana, Tridax esculenta, Chromolaena odorata) mais également dans les champs de Manihot esculenta. Les feuilles de ces espèces contribuent a la croissance de Zonocerus variegatus(Okonji et al, 2013) Cela démontre le caractère polyphage du criquet puant. Des études réalisées parJames et al (2015) ont montré que Zonocerus variegatus était attiré par différentes plantes contenants des alcaloïdes de pyrrolicidines dont le criquet s'en sert pour se protéger chimiquement ainsi que ses oeufs contre les parasites.…”
unclassified
“…The specific activity of arginase as determined by different researchers varied from 5.21 to 40 U/mg protein (Okonji et al, 2011;Al-Saad et al, 2021). Okonji et al (2013) reported a specific activity of 3.7 U/mg of protein for grasshopper gut arginase.…”
Section: Discussionmentioning
confidence: 99%
“…The ureotelic arginases have been reported to have a molecular weight of about 130,000 daltons while the uricotelics arginases possess a molecular weight of about 280,000 daltons. Ezima and Agboola (2007) Ehigie et al 2010;Okonji et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be noticed that enhancing substrate concentration enhances the rate of the reaction because of increasing the collisions between substrate and enzyme molecules until reaching a certain concentration, after that further increasing in substrate concentration has no effect on the reaction rate because that enzyme becomes saturated and its active site is occupied with substrate concentration become without effect on the reaction rate, because the enzyme becomes saturated, and the active site is occupied with the substrate [9] . Ferit [10] states that Km value for arginase purified from human vitreous humor is 6 mM to L-arginine, Okonji et al [11] and Okonji, et al, [12] report that K m value to L-arginine monochloride is 250mM, with Vmax of 6.7 µg /min for arginase purified from the gut of grasshopper, and found that the K m value is 66.7 mM for arginase purified from liver of tortoise. Ezima et al, [13] found that the K m to be 17mM for arginine and Vmax value to be 1.39 µmole ml -1 min -1 for arginase purified from fruit bat liver.…”
Section: Kinetic Constants Of Arginasementioning
confidence: 99%